Barriers to Uptake of Eyecare Services amongst Commercial Truck-Drivers in North India: A Cross-Sectional Survey (Indian Journal of Public Health Research & Development, 2020)
Purpose: Determining barriers to eyecare amongst commercial truck-drivers in north India.Method: Cross-sectional survey of 90 truck-drivers, of which 3 had visited a permanenteyecare facility before. Data was collected from the remaining 87, via a structured pretested questionnaire assessing demographics, previous eye check-ups, and eyecare awareness.Results: 33.3% (95% CI:23.6-44.3%; n=29/87) drivers had never felt any need to undergo eyeexaminations and 53 out of the 87 (60.7%; 95% CI:49.9-71.2%) were unaware of the importanceof undergoing routine eye examinations. These identified barriers to uptake of eyecare serviceswere not associated with drivers’ age, education level, marital status, or distance driven. 60.3% ofdrivers who marked lack of awareness and 68.9% of drivers who marked unfelt need as a barrier,were either illiterate, or educated only upto primary level. Cost of availing eyecare servicesand available time to undergo routine eye examination were least frequently marked barriers.Conclusion: Drivers were unaware of the importance of undergoing routine eye examinations, with youngerones feeling no need to undergo one at all. Addressing these barriers could help improve eyecare serviceutilization amongst truck-drivers.
Keywords: Truck-drivers, Eyecare services, Barriers, Awareness